2017
DOI: 10.3389/fcimb.2017.00276
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation and Infection: Molecular Mechanisms Associated with Dysfunction of Neurovascular Unit

Abstract: Neuroinflammation is a complex inflammatory process in the central nervous system, which is sought to play an important defensive role against various pathogens, toxins or factors that induce neurodegeneration. The onset of neurodegenerative diseases and various microbial infections are counted as stimuli that can challenge the host immune system and trigger the development of neuroinflammation. The homeostatic nature of neuroinflammation is essential to maintain the neuroplasticity. Neuroinflammation is regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(99 citation statements)
references
References 210 publications
(238 reference statements)
4
87
0
8
Order By: Relevance
“…Indeed, CECs exposed to the cytokines TNFα or interleukin‐6 express fewer interendothelial proteins and have greater reactive oxygen species generation, leading to increased BBB permeability . Furthermore, CECs can be activated by cytokines that are either present in the blood or released by circulating immune cells in intimate contact with CECs, to produce secondary signaling molecules (e.g., additional cytokines, prostaglandin E 2 , nitric oxide) which interact with cells within the brain to alter NVC responses . Consistent with this suggestion, in a mouse model of cholestatic liver disease, we have shown that activated monocytes within the cerebral circulation adhere to CECs and induce CEC activation through TNFα–TNF receptor‐1 interactions .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Indeed, CECs exposed to the cytokines TNFα or interleukin‐6 express fewer interendothelial proteins and have greater reactive oxygen species generation, leading to increased BBB permeability . Furthermore, CECs can be activated by cytokines that are either present in the blood or released by circulating immune cells in intimate contact with CECs, to produce secondary signaling molecules (e.g., additional cytokines, prostaglandin E 2 , nitric oxide) which interact with cells within the brain to alter NVC responses . Consistent with this suggestion, in a mouse model of cholestatic liver disease, we have shown that activated monocytes within the cerebral circulation adhere to CECs and induce CEC activation through TNFα–TNF receptor‐1 interactions .…”
Section: Discussionsupporting
confidence: 78%
“…(37) Furthermore, CECs can be activated by cytokines that are either present in the blood or released by circulating immune cells in intimate contact with CECs, to produce secondary signaling molecules (e.g., additional cytokines, prostaglandin E 2 , nitric oxide) which interact with cells within the brain to alter NVC responses. (38,39) Consistent with this suggestion, in a mouse model of cholestatic liver disease, we have shown that activated monocytes within the cerebral circulation adhere to CECs and induce CEC activation through TNFα-TNF receptor-1 interactions. (40,41) This immune cell and TNFα-driven CEC activation up-regulates CECs' inducible nitric oxide synthase expression and is directly linked to activation of microglia within the brain (especially those cells in close proximity to blood vessels) (40) and ultimately to altered behaviors expressed by cholestatic mice.…”
Section: Resting-state Hemodynamic Coherencesupporting
confidence: 69%
“…This increased innate immune response led to consequent up-regulation of numerous genes within the neuroinflammation signaling pathway (z-score = 3.6), likely establishing inflammation processes in the frontal cortex of the SIV-infected DV macaques (Table S3). Neuroinflammation signaling pathway plays a key role in maintaining the homeostasis of CNS, functioning to remove damaging agents, such SIV in this case, and clear injured neural tissues (Tohidpour et al, 2017). Excessive cell and tissue damage can ensue recruitment of microglia and enhancement of their activities, which exacerbates neuronal damage and ultimately results in chronic inflammation with necrosis of glial cells and neurons (Wang et al, 2015).…”
Section: Inflammation As Results Of Intensification Of the Innate Immumentioning
confidence: 99%
“…Neuroinflammation triggered by pro‐inflammatory molecules causes increased permeability of the BBB, resulting in immune cell infiltration, exacerbation of the inflammatory response, leading to reactive gliosis, and eventually causing neurodegeneration . Bacteroidetes is a family of Gram‐negative bacteria, and thus have lipopolysaccharide (LPS) as the major outer membrane component, which can trigger systemic inflammation and promote the release of pro‐inflammatory cytokines .…”
Section: Intestinal Microbiome Alterations and Admentioning
confidence: 99%